Analysis of The Quran Isyarat Learning Management at The Magelang Deaf Education Foundation - Sasongko, M. Beni; Usman, Nurodin (Al Ulya: Jurnal Pendidikan Islam, 2025)
Learning the Quran for people with disabilities is carried out with management that is by the conditions of the students. The process of learning the sign Qur'an for deaf students is carried out using the Kitabah and Tilawah method which is expected to make it easier and faster for students to read. This study aims to describe the application of Kitabah and Tilawah for deaf students in reading the Quran, and to describe the supporting and inhibiting factors in the process of learning the Quran Isyarat at the Magelang Deaf Education Foundation. The method used in this study is descriptive qualitative research. The object of this study is students at the Magelang Deaf Education Foundation. The results of the study indicate that (1) the Kitabah and Tilawah method can help and make it easier for students to read the Quran Isyarat. (2) Learning the Quran for deaf students faces many obstacles, namely a lack of sincerity, such as no enthusiasm for memorizing, lack of concentration such as when other students memorize, it turns out that someone is talking or chatting with their friends, so that the other students' concentration is divided. The supporting factors are good motivation from the participants, regular guidance from the teachers, and long experience from the institution in managing learning. Teachers are asked to have stronger patience when providing motivation and guiding deaf participants at the Magelang Deaf Education Foundation.